Structural Changes in Insulin at a Soft Electrochemical Interface - Lamichhane, Hum Bahadur; Henares, Terence G; Hackett, Mark; Arrigan, Damien (AMER CHEMICAL SOC, 2021)
Understanding the interaction of proteins at interfaces, which occurs at or within cell membranes and lipoprotein vesicles, is central to our understanding of protein function. Therefore, new experimental approaches to understand how protein structure is influenced by protein-interface interactions are important. Herein we build on our previous work exploring electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) to investigate changes in protein secondary structure that are modulated by protein-interface interactions. The ITIES provides an experimental framework to drive protein adsorption at an interface, allowing subsequent spectroscopic analysis (e.g., Fourier transform infrared spectroscopy) to monitor changes in protein structure. Here, we reveal that the interaction between insulin and the interface destabilizes native insulin secondary structure, promoting formation of α helix secondary structures. These structural alterations result from protein-interface rather than protein-protein interactions at the interface. Although this is an emerging approach, our results provide a foundation highlighting the value of the ITIES as a tool to study protein structure and interactions at interfaces. Such knowledge may be useful to elucidate protein function within biological systems or to aid sensor development.